Analysis of Service Quality and Brand Image with the Mediation of Emotional Experience Variables on the Impact of Customer Loyalty in Informal Restaurants in North Jakarta - Mercya Mollisca Gunawan; Patricia Hermawan; Vasco A. H. Goeltom; V. Nonot Yuliantoro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of service quality and brand image on customer loyalty in informal restaurants in North Jakarta, using emotional experience as a mediating variable. This study was conducted at informal restaurants in the Pantai Indah Kapuk (PIK) area, which is one of the main culinary destinations. The research method uses a quantitative approach with the PLS-SEM analysis tool. Data were collected from 200 respondents through a questionnaire measured using a Likert scale of 1-5. The results of the study indicate that service quality and brand image have a significant positive effect on customer loyalty, both directly and through emotional experience. This study provides academic contributions in expanding studies related to customer loyalty in the culinary sector, as well as practical recommendations for industry players to improve customer emotional experiences to strengthen loyalty.